Integrated inventory system for forecasts based on knowledge management for the reduction of stock breaks in a distribution SME - Bonett, Johan (2019)
In the current market, there is a large number of SMEs that have a large margin of economic losses due to lack of stocks, due to the supply process. In other words, the lost sales and the costs of the services generated by not having their products available in their warehouses is a critical scenario in the distribution companies, whose added value lies in maximizing their level of customer service. To solve this problem, we propose a system that integrates the development of the attention and the model of the inventories of the periodic review, the bases based on the framework of the work. The results, after analyzing the demand, their patterns and choosing the best method to use, are antecedents to develop the management of inventories and their policies. Likewise, knowledge management will act as an integrated support. Through the simulation carried out for a distribution of lubricants, results were obtained that indicate a reduction of 93% in losses due to stock-outs and an increase in the service level that goes from 77% to 91%. This is an integrated system of interest to be applied as a solution for SMEs that have high stock-outs and lack this type of tools..